2003
DOI: 10.1007/978-3-642-55519-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of Marine Sponges

Abstract: ABSTRACT16S rDNA library construction revealed a uniform microbial community in sponges that were collected from different oceans. Altogether 14 monophyletic, sponge-specific sequence clusters were identified that belong to at least seven different bacterial divisions. By definition, the sequences of each cluster are more closely related to each other than to a sequence from non-sponge sources. These monophyletic clusters comprise 70 % of all publicly available, sponge-derived 16S rDNA sequences reflecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
239
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(250 citation statements)
references
References 84 publications
8
239
1
2
Order By: Relevance
“…There are four notable exceptions with much fewer Plus-OTUs: Polymastia sp., Cymbastela coralliophila, Stylissa massa and Xestospongia sp. A possible explanation, at least for the first two mentioned sponges, is that they are low microbial abundance sponges that contain less diverse microbiota with a different compositional profile to high microbial abundance sponges (Hentschel et al, 2003;Kamke et al, 2010). The core bacterial community consists of only three 97%, eight 95% and 18 different 90% OTUs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four notable exceptions with much fewer Plus-OTUs: Polymastia sp., Cymbastela coralliophila, Stylissa massa and Xestospongia sp. A possible explanation, at least for the first two mentioned sponges, is that they are low microbial abundance sponges that contain less diverse microbiota with a different compositional profile to high microbial abundance sponges (Hentschel et al, 2003;Kamke et al, 2010). The core bacterial community consists of only three 97%, eight 95% and 18 different 90% OTUs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…They are ecologically important and a rich source of novel, biotechnologically relevant natural products. The association of some species with dense and complex microbial consortia has long been recognized (Vacelet 1975;Vacelet and Donadey 1977;Wilkinson et al, 1981) and these sponges were termed bacteriosponges or 'high microbial abundance' sponges to distinguish them from co-occurring sponges in the same habitat that lack dense microbial communities (which were thus termed 'low microbial abundance' sponges) (Reiswig 1981;Hentschel et al, 2003). In high microbial abundance sponges, microbes can comprise as much as 40% of the sponge biomass and represent a variety of different morphotypes (Vacelet 1975).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the phylum Chloroflexi was found only in young biofilms. This photoheterotrophic phylum is usually associated with sponges, corals, and filamentous biofilms (Hentschel et al, 2003;Okabe et al, 2005;Ishii et al, 2008;Apprill et al, 2009); some Chloroflexi have been reported to express antisettlement activity against H. elegans . The presence of these inhibitive strains may help to explain the low settlement inductiveness of the young biofilm extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, two general categories were identified that were termed "bacterial sponges" and "non-symbiont harboring, normal sponges" (Reiswig, 1981). Later on, the terms "low microbial abundance" (LMA) and "high microbial abundance" (HMA) sponges were coined to acknowledge the additional presence of archaea in sponge tissues (Hentschel et al, 2003). A typical HMA sponge contains 10 8 to 10 10 microorganisms/g sponge tissue, which can make up to 20%-35% of the sponge biomass (Reiswig, 1981;Webster et al, 2001;Hentschel et al, 2012); in contrast, only 10 5 to 10 6 bacteria/g sponge tissue are found in LMA sponges, which is roughly equivalent to the microbial abundances in seawater (Hentschel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%